2019
DOI: 10.1177/1523422319851274
|View full text |Cite
|
Sign up to set email alerts
|

The Agency of the Principal–Agent Relationship: An Opportunity for HRD

Abstract: The Problem Agency theory has been empirically studied in other fields of study such as economics, political science, sociology, and management. Although a proposal for inclusion of agency theory to test training and development outcomes was made in human resource development (HRD)-related publications, little research has been conducted and published in HRD-related literature. The Solution This review of agency theory offers a description of the elements and factors associated with the principal–agent relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 78 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…According to Baker (2019) that the concept that describes the relationship between the grantor principal (contract) and the agent (the recipient of the contract), agency theory is a relationship between shareholders as principals whereas the management as the agent. The conclusion that can be drawn from some of the expert opinions above is that agency problems occur when the company leader as the principal wants to make tax payments efficient in order to gain profits by avoiding taxation related to differences in executive character and the number of assets.…”
Section: A Agency Theorymentioning
confidence: 99%
“…According to Baker (2019) that the concept that describes the relationship between the grantor principal (contract) and the agent (the recipient of the contract), agency theory is a relationship between shareholders as principals whereas the management as the agent. The conclusion that can be drawn from some of the expert opinions above is that agency problems occur when the company leader as the principal wants to make tax payments efficient in order to gain profits by avoiding taxation related to differences in executive character and the number of assets.…”
Section: A Agency Theorymentioning
confidence: 99%
“…A conceptual study has also been carried off to critically review the AT theory, and this study has also indicated that the AT theory seems unrealistic to support the idea that individuals and organizations are primarily motivated by financial gain, rather individuals can also be motivated by status, their community, and their need for self-fulfillment (Zogning, 2017). Besides, an empirical study has been carried off to assess AT theory to training and development outcomes; and this study result has indicated that much of the theoretical implications of the AT theory are transferable to human resource development (Baker, 2019). However, according to the present knowledge of the researcher, there is no study so far conducted in the country on the effectiveness of AT related to performance enhancement in the PS.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…The antecedents built by the three previous studies have the same common thread in a form of derivation, namely from the context of the application of knowledge management (KM) (Games & Rendi, 2019), through the human resource development (HRD) approach (Baker, 2019), and more specific to intellectual capital management (Henri et al, 2017). The similarity of the three studies above each uses a consequent variable of financial performance.…”
Section: Fathanah Responsive Leadership: As a Supplement In The Satel...mentioning
confidence: 99%
“…Therefore, in our opinion, the fathanah character is more needed in the context of KM, HRD, and intellectual capital than tabligh. (Baker, 2019). The agency problem is a possible conflict of interest that may occur between the principal and the agent.…”
Section: Human Resource Development Managementmentioning
confidence: 99%